Design Comparison between the Gravity and Pressure Sand Filters for Water Treatment, Review (Journal of Engineering, 2023)
Hygienic engineering has dedicated a lot of time and energy to studying water filtration because of how important it is to human health. Thorough familiarity with the filtration process is essential for the design engineer to keep up with and profit from advances in filtering technology and equipment as the properties of raw water continue to change. Because it removes sediment, chemicals, odors, and microbes, filtration is an integral part of the water purification process. The most popular technique for treating surface water for municipal water supply is considered fast sand filtration, which can be achieved using either gravity or pressure sand filters. Predicting the performance of units in water treatment plants is a basic principle. For that reason, this research was executed to compare gravity and pressure sand filters in terms of construction, use, efficiency, filtration rate, cost, benefit, and drawbacks to predict the performance of those units under different conditions and from an economic standpoint. It also served as a presentation and review of previous studies dealing with the evaluation and development of pressure and gravity filters. This paper gives a brief overview of filtration theory, the types and properties of filter media, filter backwashing, and operational problems that can be avoided in the filtration process.